FACTORS AFFECTING MSME’s INTEREST TO APPLY FOR BUSINESS FINANCING IN ISLAMIC FINANCIAL INSTITUTIONS - Rohmah, Mayda Miftakhur; Rintasari, Nugraheni (Muhammadiyah International Journal of Economics and Business, 2018)
This  study  aims to  determine the  effect of  services, procedure,  reputation,  and promotion  on  the MSMEs? interest to  apply  for  business financing  provided  by  Islamic  financial  institutions.  It is  a quantitative  research. The  data were primary  data obtained  from  questionnaires  that were distributed directly to the  respondents. As  many  as 58  MSME  actors in  the Manding  Leather Craft  Center, Bantul,  Indonesia,  were involved  as the respondents.  The  sampling  technique  was purposive sampling  as a type  of  the non  probability  sampling  method.  Data  analysis  methods included  multiple  linear  regression,  classical assumption  test,  and  hypothesis  testing  (t-test  and F-test). Data  processing  required the assistance of  SPSS  17.0.   The  results of  the t-test  show  that each independent  variable  partially  affects the MSMEs?  interest to  apply  for  Islamic  financing. Furthermore, the results of the F-test indicate that the variables of services, procedure, reputation, and promotion simultaneously affect the MSMEs?interest  to apply for business financing provided by  Islamic  financial  institutions.